Seismic Fragility Assessment for a Newly Developed Buried Arch Bridge - Dang, Phu Van; Huh, Jungwon; Ahn, Jin-Hee; Haldar, Achintya; Kwak, Kiseok (KSCE journal of civil engineering, 2023)
This study aims to assess the seismic response of a newly developed buried arch bridge system. The proposed buried arch bridge system is comprised of precast concrete panels, external steel outriggers, and steel V-strips to solve the limitation encountered in the storage, transportation, and construction of traditional buried arch structures. The three-dimensional finite element analysis of this arch system is conducted under dynamic analysis emphasizing the frequency content of earthquakes. Then, the fragility curves are suggested for this arch system based on two damage states defined via incremental dynamic analysis. The results show that this proposed arch system is significantly affected under a high frequency content earthquake compared to the low and intermediate ones. Additionally, the arch system deflects the most at the mid-high position rather than at the arch crown. The deflection at the arch crown or at the mid-high position can be used for establishing the fragility curves as they both connect with the failure mechanism of the arch structure.